2014
DOI: 10.1007/s15010-014-0683-4
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin levels predict severe dengue

Abstract: On the basis of this diagnostic efficiency, we propose that ferritin may serve as a potential biomarker for an early prediction of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 30 publications
9
71
0
1
Order By: Relevance
“…For example, infections caused by the Dengue virus and Mycobacterium tuberculosis result in increased levels of ferritin 49,50 and increased host cell uptake of iron. Similarly, Chlamydia infection results in decreased ACO1 activity and thereby increased ferritin levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, infections caused by the Dengue virus and Mycobacterium tuberculosis result in increased levels of ferritin 49,50 and increased host cell uptake of iron. Similarly, Chlamydia infection results in decreased ACO1 activity and thereby increased ferritin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally it is important to note that serum ferritin is a marker of macrophage activation in vivo , and is often elevated in dengue patients [7,8]. Level of serum ferritin in often higher in pediatric dengue patients as compared to adults [43].…”
Section: Discussionmentioning
confidence: 99%
“…Roughly 5% of clinically-apparent dengue cases will progress to severe dengue, which is characterized by plasma leakage leading to effusions, respiratory difficulty, hypovolemic shock, and hemorrhage [5]. Recent investigations have demonstrated that higher serum ferritin levels are associated with dengue as compared to other acute febrile illnesses, and that degree of elevation of ferritin is associated with disease severity and a pro-inflammatory cytokine profile [7, 8]. Similar to hemophagocytic syndromes, infection with either DENV or EBV results in a genetic immune response profile that is associated with uncontrolled inflammatory responses [9], and these immunologic pathways may be common to those that lead to the development of acquired HLH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, circulating ferritin in HIV patients ranges around a median of 487 μg/L and has been associated with HIV disease progression [54, 55]. The most striking elevation of circulating ferritin is seen in patients suffering from acute dengue infections, with median plasma ferritin levels up to 1,264 μg/L [56, 57]. Moreover, circulating levels of both IL-18 and ferritin show strong correlation with dengue disease severity and, therefore, may be considered as a tool to predict disease progression [57, 58].…”
Section: Plasma Inflammatory Profiles In Viral and Bacterial Infectionsmentioning
confidence: 99%